Monitoreo en tiempo real de la salud estructural de puentes (MSE) para la detección temprana de fallas mediante un prototipo de red de sensores inalámbricos ubicados en el puente del Río Boquerón-Catamayo. - Quinde Granda, Valeria Estefania (2016)
The present project presents a concise literature review regarding the structural health monitoring of a bridge, taking as an introductory literature the elements that constitute a bridge, such as: superstructure, substructure and access, and mainly variables internal as external ones that affect the structural health of the same, which allow the correct selection of the monitoring instruments. The technology that allows the monitoring of structural health plays an important role, since the selection of the necessary instrumentation will depend on the type of technology to be applied, that is why it is presented an investigation about the types of technologies that allow the monitoring of structures, based on the monitoring requirements, considering also the standards that allow wireless communication between the instruments used for monitoring, as well as the distances and frequencies in which these operate. In the same way, a simulation of the network is presented through the opnet simulation software in order to know the scope of a node with respect to the other, the way in which each of these nodes are constituted and mainly the topology that presents greater advantages in terms of delay, throughput and reception of data. It is also highlighted the way in which each node forming the network is constituted in which the module xbee pro s2b allows the establishment and communications of the same, the calculation of the power level of reception of the coordinating node to 100 meters of scope and the way in which the application was developed that makes it possible to obtain information in real time about the conditions of the structure in vs express 2015 software. Finally, we present in detail the curves obtained in the coordinating station regarding the stability in three specific points of the structure, which are: left stirrup downstream, right stirrup downstream and central part, vibration time, humidity and temperature present in the same, as well as the interpretation of these curves.